Developing Students’ Reading Comprehension Abilities Using The Reading Workshop Learning Model in Students of Class IV of State Elementary Number 101992 Cimahi, Bangun Purba Distric in The Academic Year 2024-2025 - Sutikno; Darmainur (PT Inovasi Pratama Internasional, 2025)
The reading ability of elementary school students in Indonesia remains low, which was the main focus of this study. Therefore, this study will try to explain the factors that cause low reading ability of elementary school students, especially in Public Elementary School Number 101992, Cimahi, Bangun Purba District. This study was designed to provide an alternative reading teaching method that has the potential to improve reading comprehension skills. The application of this alternative is a reading-workshop reading-learning model. The problem in this study is: (a) What are the initial and final reading abilities of students at Public Elementary School Number 101992, Cimahi, Bangun Purba District, using the reading workshop model? (b) Can the Reading Workshop model improve students' Elementary School Number 101992 Cimahi, (c) Is reading abilities? (d) What are the qualities (weaknesses and strengths) of the Reading Workshop model for teaching students to read?Public Elementary School Number 101992, Cimahi, Bangun Purba District?. This study used a quasi-experimental method with a one-group pretest-posttest design. The research techniques used in this study were: (1) tests, (2) questionnaires, (3) observations, and (4) the Reading Workshop teaching model. This study was conducted in Class IV Public Elementary School Number 101992 in Cimahi, Bangun Purba District, China. The findings of this study show a significant difference between the final and initial abilities to read. There was a significant difference between the final and initial abilities in the reading comprehension of grade IV students. Public Elementary School Number 101992 Cimahi, Bangun Purba District, because t count (2.78) > t table (2.66) at p < 0.05 in db 58. This means that reading comprehension learning through a reading workshop for elementary school students is effective in improving their reading ability